The Hoji Ritual in My Life - Kibi, Akira (Revista Espaço Acadêmico, 2021)
“What are your plans for this weekend?” a friend of mine asked me, two years ago. “We are going to hold a Hoji-party (or service) on behalf of my mother. Since she knew my mother has been dead for many years, she asked more details about Hoji, and I explained that it is a Buddhists’ reunion among family members and relatives in commemoration of the deceased.